Automotive Brake Friction Part Recovery Technology Using Composite Materials (Zien Journal of Social Sciences and Humanities, 2021)
The composition will consist of at least two components among the materials. There are composite materials - for example, there are plywood. In all other composites, the components can be divided into a matrix or a connector, and electrical energy - to fill. Composites are usually distinguished by the type of reinforcing filler or the substance of the Matrix.